PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS ARTIFICIAL INTELLIGENCE BERNUANSA ISLAMI PADA MATA KULIAH ANALISIS KOMPLEKS - Ni'am, M. Khusnun; Saputra, Ikhwan; Nisa, Zuhrotun; Mahmudah, Umi (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2024)
With the rapid development of technology, learning complex analysis has become increasingly important in keeping up with technological advancements, yet it is often overlooked. Therefore, interactive learning media such as videos integrated with artificial intelligence are needed to visualize theoretical material. This research aims to (1) describe the design of instructional videos, (2) explain the quality and validity of the development of instructional videos by experts and product trials, and (3) evaluate the effectiveness of instructional videos. The analysis used is qualitative descriptive analysis. This research employs the Research and Development (R&D) method with the ADDIE model, involving five stages: analysis, design, development, implementation, and evaluation. Instructional videos on complex analysis are deemed valid by media experts, with the product receiving favorable ratings in terms of appearance (85%), ease of use (65%), and material presentation (70%). Based on expert assessments of the content, the product is also rated well in terms of suitability (55%) and material coherence (85%). Meanwhile, assessments by language experts indicate high language appropriateness (90%), along with favorable ratings in audio pronunciation accuracy (70%) and language selection (80%). From the validation results and expert assessments, as well as trials with small and large groups, it can be concluded that the development of AI-based videos for complex analysis courses is suitable for use.